2007
DOI: 10.1016/j.jml.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additional characters on choice of referring expression: Everyone counts☆

Abstract: Two story-telling experiments examine the process of choosing between pronouns and proper names in speaking. Such choices are traditionally attributed to speakers striving to make referring expressions maximally interpretable to addressees. The experiments revealed a novel effect: even when a pronoun would not be ambiguous, the presence of another character in the discourse decreased pronoun use and increased latencies to refer to the most prominent character in the discourse. In other words, speakers were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
307
8
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(384 citation statements)
references
References 71 publications
41
307
8
8
Order By: Relevance
“…In the story-continuation experiments presented in this paper, both subject and target referents were semantically human. Different studies (Arnold & Griffin 2007) showed that the presence of multiple referents in a discourse reduces the use of less specified types of referring expressions to refer back to one of them. Even though the participants in the experiment reported here could have opted for more reduced types of referring expressions, as there was no competition between the referents in terms of gender (except for TI1 in Table (1)), they nevertheless chose more specified types of referring expressions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the story-continuation experiments presented in this paper, both subject and target referents were semantically human. Different studies (Arnold & Griffin 2007) showed that the presence of multiple referents in a discourse reduces the use of less specified types of referring expressions to refer back to one of them. Even though the participants in the experiment reported here could have opted for more reduced types of referring expressions, as there was no competition between the referents in terms of gender (except for TI1 in Table (1)), they nevertheless chose more specified types of referring expressions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This has been the most studied aspect of situated production in previous work (e.g., Griffin & Bock, 2000). Referential ambiguity is known to cause interference when producing referring expressions (Arnold & Griffin, 2007;Fukumura, Van Gompel, & Pickering, 2010); and it can be successfully resolved if detected before the production starts (Ferreira, Slevc, & Rogers, 2007). Referential competition and ambiguity resolution strategies are indexed by visual responses; here we focus on the latency of last fixation on the target object before it is mentioned.…”
Section: Research Questionsmentioning
confidence: 99%
“…On one hand, there is evidence that perceptual factors are involved in selecting referential information for sentence processing (e.g., Arnold & Griffin, 2007;Gleitman, January, Nappa, & Trueswell, 2007;Papafragou, Hulbert, & Trueswell, 2008; see also Myachykov, Thompson, Scheepers, & Garrod, 2011, for a review). On the other hand, there is also evidence for sentence processing mechanisms which explain how eye-movements and speech responses are linked (Meyer, Sleiderink, & Levelt, 1998;Griffin & Bock, 2000;Bock, Irwin, Davidson, & Levelt, 2003;Qu & Chai, 2008;Kuchinksy, Bock, & Irwin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, full comparison activity between the target and the nonreferents may be sacrificed, leading to greater overspecification. Such an account is put forward by Koolen et al (2011) who found plural targets REs to be more frequently overspecified than single target REs, and similarly by Arnold and Griffin (2007) who found more full NP expressions than appropriate pronominal expressions to plural targets.…”
Section:  the Cognitive Significance Of Overinformativenessmentioning
confidence: 99%